KRITIK SOSIAL DALAM PUISI-PUISI INDONESIA PADA MASA REFORMASI : Kajian Struktur dan Sosiologi Sastra Terhadap Karya Sastra Sebagai Alternatif Bahan Ajar Sastra di SMA - Reza, Saeful Rachman (2015)
Penelitianiniberangkatdarikeresahanpenelititerhadappembelajaransastra di sekolah yang belumberjalansecaramaksimalbiladibandingkandenganporsipembelajaranmaterikebahasaansertaperkembangansastra Indonesia saatini.Pengajaransastra di sekolahmisalnyapuisimasihterbataspadateori-teorisertaapresiasiterhadapkaryasastra yang sudahlampausehinggasiswakurangmengenalkarya-karyasastra Indonesia mutakhir.Hal tersebutsalahsatunyadisebabkanolehsedikitnyaketersediaanbahan ajar di sekolah.Olehkarenaitupenelitianiniselainmengkajikaryasastrayaknistrukturpuisi (situasibahasa, temadanpengembangantema, penggunanbahasapadapuisi, bentukpuisi) sertarepresentasikritiksosialdalampuisijugabertujuanmenciptakanalternatifbahan ajar dalamupayamemperbaikimutupembelajaransastra di sekolahkhususnyamateripeminatankemampuanbersastra di SMA. Tujuan yang ingindicapaidalampenelitianiniantara lain mendeskripsikan(1) strukturpuisi-puisi Indonesia masareformasi yang bertemakritiksosial, (2)representasikritiksosialdalamPuisi-puisiIndonesia masareformasi, (3) mendeskripsikanpemanfaatanpuisi-puisi Indonesia masareformasibertemakritiksosialsebagaiAlternatifBahan Ajar Sastra di SMA. Metode yang digunakandalampenelitianiniadalahmetodeanalisisisi.Adapunobjekuntukpenelitianiniadalahpuisi-puisikaryaparapenyair Indonesia yang bertemakritiksosial.Rentangwaktu yang dipilihadalahmasareformasiyaknisejaktahun 1998 sampaitahun 2013 karenapadarentangwaktutersebuttelahterjadiberbagaiperistiwasosial, budaya, sertapolitik di Indonesia. Hasilpenelitianiniantara lain (1) darikajianstrukturpuisiditemukanbahwaseluruhsituasibahasadalampenelitianiniadalah monolog danhampirseluruhpuisimemilikipembicaradanpendengardalamteks, lalutemaseluruhpuisidalampenelitianiniadalahkritiksosial, selainitudalampuisi-puisi yang menjadiobjekpenelitianterdapatgejalabunyisepertiorkestrasiefonidankakafoni, selainituterdapatrimaasonansidanaliterasi, secarasintaktikditemukanbangunkalimattanya, kalimatperintah, kalimatberita, strukturkalimatsederhanadankalimatluas, sertatipografipuisi yang sederhana. (2) kritiksosial yang terepresentasidalampuisi-puisi yang menjadiobjekpenelitianantara lain kritikterhadappermasalahankemiskinan, kejahatan, disorganisasikeluarga, permasalahanbirokrasi, permasalahanlingkunganhidup, permasalahangenerasimuda di era modern. Kritiksosialterhadappermasalahansosialmerupakan yang paling banyakditemukan. (3) hasilkajianterhadapstrukturdankritiksosialselanjutnyadigunakandalampenyusunanalternatifbahan ajar berupamoduluntukpembelajaransastrayaknipeminatan di SMA. berdasarkanhasilpenelaahan yang dilakukanolehtigapraktisiyakni guru matapelajarandidapatkansimpulanbahwamodultersebutdapatdigunakansebagaialternatifbahan ajar di SMA. This study departs from the unrest researchers to study of literature in schools that have not run optimally compared with the share of language learning materials as well as the development of Indonesian literature today . Teaching literature in schools such poetry is still limited to the theories and appreciation of literary works that have been past so that students are less familiar with the works of Indonesian contemporary literature . This is one of them caused by at least the availability of teaching materials in schools . Therefore, this study examines the literature other than the structure of the poem ( the language situation , themes and theme development , the use of language in poetry , poetry form ) as well as the representation of social criticism in the poem also aims to create an alternative teaching materials in an effort to improve the quality of teaching literature in schools , especially specialization material compose capabilities in high school. The aim of this research , among others describe ( 1 ) the structure of the poems Indonesia reform period themed social criticism , ( 2 ) the representation of social criticism in the poems Indonesia reform period , ( 3 ) describe the use of poetry Indonesia reform period themed social criticism as Alternative Instructional Materials Literature in high school. The method used in this study is a content analysis method . The object of this study is the poetry of the poet Indonesia themed social criticism . Selected time range is the reform period from 1998 until 2013 due to the time span there have been many social events , culture , and politics in Indonesia. The results of this study are (1) the study of the structure of the poem was found that all the language situation in this study is a monologue and almost the whole poem has a speaker and a listener in the text, and the theme of the whole poem in this research is a social critique, as well as in the poems the research object and the symptoms sound like orchestration efoni and kakafoni, besides there is rhyme assonance and alliteration, syntactically found wake interrogative sentence, the sentence order, news sentences, simple sentences and sentence structure widely, and typography simple poetry. (2) social critique poems represented in the research object among other criticisms of the problems of poverty, crime, family disorganization, bureaucratic issues, environmental issues, problems of young people in the modern era. Social critique of the social problems are the most common. (3) the results of the study on the structure and social criticism subsequently used in the preparation of teaching materials in the form of alternative learning modules for the specialization in high school literature. based on a review conducted by the three practitioners that teachers of subjects obtained the conclusion that the module can be used as an alternative teaching materials in high school.